Ultrahigh-strength concrete containing self-made lightweight aggregate and preparation method thereof
By combining self-made lightweight aggregate with high-efficiency polycarboxylate superplasticizer and slag powder, the problem of weak bonding between lightweight aggregate and cement matrix was solved, resulting in lightweight and high-strength concrete, which improved construction quality and service life. At the same time, it made resource-efficient use of waste materials, which is in line with sustainable development.
Patent Information
- Application Number
- CN202511631377.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-10
- Publication Date
- 2026-02-06
AI Technical Summary
Existing concrete methods, such as adding lightweight aggregates or increasing the amount of cementitious materials, can reduce self-weight or increase strength, but it is difficult to simultaneously meet the engineering requirements of lightweight and ultra-high strength. The weak interfacial bonding between lightweight aggregates and cement matrix easily leads to stress concentration points, and the increased heat of hydration and shrinkage result in a decline in overall performance.
The self-made lightweight aggregate is made from waste glass particles, fly ash, metakaolin and plant fibers. It is calcined at high temperature to form a porous structure that is tightly bonded to the cementitious material. Combined with high-efficiency polycarboxylate superplasticizer and slag powder, the water-cement ratio is controlled to achieve high strength and low density.
While reducing the density of concrete, it maintains ultra-high compressive strength, improves construction quality and efficiency, extends the life of building structures, and realizes the resource utilization of industrial waste, which is in line with the concept of sustainable development.
Smart Images

Figure CN121470844A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of concrete technology, and more specifically, to an ultra-high strength concrete containing self-made lightweight aggregate and a method for preparing the same. Background Technology
[0002] Concrete is an artificial stone material made by mixing cementitious materials, fine aggregates, coarse aggregates, and water in a certain proportion, and then hardening it through mixing, pouring, and curing. It is widely used in civil engineering projects such as buildings, bridges, roads, and dams. Its performance can be improved by adjusting the mix proportion or adding admixtures to meet the requirements of different projects for strength, durability, and impermeability. Concrete has the advantages of abundant raw materials, low cost, strong plasticity, high compressive strength, and good durability. However, it is heavy and has relatively low tensile strength, so it often needs to be combined with steel bars to form reinforced concrete structures to improve its integrity and seismic resistance.
[0003] The relevant concrete reduces its self-weight or increases its strength by adding lightweight aggregates or increasing the amount of cementitious materials. However, the interface between lightweight aggregates and cement matrix is weak and easily forms stress concentration points. At the same time, the use of a large amount of cementitious materials will lead to increased heat of hydration and increased shrinkage, resulting in a decline in the overall performance of concrete and making it difficult to meet the engineering requirements of lightweight and ultra-high strength at the same time. Summary of the Invention
[0004] To address the problem that the overall performance of concrete deteriorates due to the addition of lightweight aggregates or the increase of cementitious materials to reduce its self-weight or increase its strength, making it difficult to simultaneously meet the engineering requirements of lightweight and ultra-high strength, this application provides an ultra-high strength concrete containing self-made lightweight aggregates and its preparation method.
[0005] In the first aspect, this application provides an ultra-high strength concrete containing self-made lightweight aggregate, employing the following technical solution: An ultra-high strength concrete containing self-made lightweight aggregate is made from raw materials containing the following components, per cubic meter of concrete: 300-350 kg of high-strength grade cement, 10-15 kg of high-efficiency polycarboxylate superplasticizer, 80-120 kg of slag powder, 500-800 kg of self-made lightweight aggregate, and 150-180 kg of water.
[0006] By adopting the above technical solution, a cementitious system is formed by high-strength grade cement and slag powder, while a high-efficiency polycarboxylate superplasticizer reduces the water-cement ratio. At the same time, self-made lightweight aggregate is used as a lightweight filler material. The synergistic effect of the three enables the concrete to achieve high strength while maintaining a low self-weight.
[0007] Preferably, the self-made lightweight aggregate is made from raw materials comprising the following parts by weight: 32-65 parts waste glass particles, 16-39 parts fly ash, 12-33 parts metakaolin, and 2-10 parts plant fiber.
[0008] By adopting the above technical solution, waste glass particles are melted and bonded as siliceous raw materials at high temperature, while fly ash and metakaolin undergo a polymerization reaction in an alkaline environment to form a solid skeleton. At this time, plant fibers decompose at high temperature, leaving uniform pores, thus the lightweight aggregate obtains the characteristics of low density and high strength.
[0009] Preferably, the particle size of the waste glass particles is 1-5 mm; the fineness of the fly ash is such that the residue on a 45 μm square-hole sieve does not exceed 30%.
[0010] By adopting the above technical solutions, the particle size of waste glass particles is controlled within the range of 1-5mm to achieve uniform distribution of the molten liquid phase during the calcination process; while the fineness control of fly ash ensures that it has high reactivity, which is conducive to its interaction with metakaolin and activators, thereby improving the overall performance of lightweight aggregate.
[0011] Preferably, the specific surface area of the metakaolin is 500-800 m². 2 / kg; the length of the plant fiber is 5-10mm.
[0012] By adopting the above technical solutions, metakaolin, which has a high specific surface area, can enhance the cementitious activity and reaction rate of aggregates; the plant fiber length is controlled at 5-10 mm, which helps it to be evenly dispersed in the mixture and form interconnected micropores after high-temperature treatment, thereby improving the internal structure of lightweight aggregates.
[0013] Secondly, this application provides a method for preparing ultra-high strength concrete containing self-made lightweight aggregate, using the following technical solution: A method for preparing ultra-high strength concrete containing self-made lightweight aggregate includes the following steps: S1. Preparation of homemade lightweight aggregate: S1.1 Raw material pretreatment: First, collect waste glass and remove impurities before crushing it; at the same time, collect fly ash and prepare metakaolin, and cut plant fibers into small pieces for later use. S1.2 Raw material mixing: Take waste glass particles, fly ash, metakaolin and plant fiber and mix them in a mixer for 3-5 minutes to make the raw materials initially evenly mixed; S1.3, Slurry preparation: Add water and activator to the mixed dry material obtained in step S1.2, and continue stirring for 8-12 minutes to form a slurry; S1.4 Preliminary hardening: Pour the slurry obtained in step S1.3 into a mold and cure it in a curing chamber to obtain a preliminarily hardened block. S1.5 Cutting and shaping: Take the block obtained in step S1.4 out of the mold and cut it into blanks; S1.6 High-temperature calcination: The green body obtained in step S1.5 is heated and kept at a certain temperature, and then cooled to room temperature in the furnace to obtain the self-made lightweight aggregate; S2, Concrete mixing: S2.1 Dry mixing: Take the self-made lightweight aggregate, high-strength grade cement and slag powder prepared in step S1 according to the proportion and dry mix for 3-5 minutes to obtain the mixed dry material; S2.2 Wet mixing: Dissolve the high-efficiency polycarboxylate superplasticizer in water, and then slowly add the solution to the mixed dry materials. Wet mix for 8-12 minutes to obtain the concrete mixture. S3. Molding and Curing: The concrete mixture is poured into a mold, vibrated to form the concrete, and then cured to obtain ultra-high strength concrete.
[0014] By adopting the above technical solution, the self-made lightweight aggregate uses waste glass as the main source of silicon and aluminum. Fly ash and metakaolin undergo a polymerization reaction under alkali activation to form a matrix with cementitious properties, which encapsulates and binds the glass particles together. At the same time, plant fibers decompose and escape during high-temperature calcination, forming a porous structure inside the aggregate, thereby reducing the apparent density of the aggregate. Subsequently, during the high-temperature calcination stage, the surface of the glass particles partially melts and reacts with the cementitious phase to form a solid interface to improve the overall strength of the aggregate. Then, in the concrete mixing stage, the lightweight aggregate works synergistically with high-strength cement and slag powder. The slag powder can participate in the secondary hydration reaction, fill the interface transition zone, and improve the density. By adding a high-efficiency polycarboxylate superplasticizer to reduce the water-cement ratio, the workability of the concrete mixture is ensured while improving the final mechanical properties. Subsequently, during the molding and curing process, high-temperature curing promotes the continuous hydration of the cementitious materials, enabling the compressive strength and development rate of the concrete to meet the requirements of ultra-high strength.
[0015] Preferably, in step S1.3, water accounts for 15%-20% of the total mass of the mixed dry materials, while the activator accounts for 3%-5% of the total mass of the mixed dry materials.
[0016] By adopting the above technical solution, the amount of water added is controlled within a certain range to ensure that the slurry has a certain fluidity for molding, while avoiding excessive water content that would lead to excessively high porosity. At the same time, adjusting the content of activator helps to promote the polymerization reaction of fly ash and metakaolin, further improving the strength of lightweight aggregate.
[0017] Preferably, in step S1.3, the activator is a mixed solution of sodium hydroxide and sodium silicate.
[0018] By adopting the above technical solution, sodium hydroxide provides an alkaline environment to activate the activity of cementitious materials, while sodium silicate acts as a structure directing agent to promote the formation of aluminosilicate networks. The two work synergistically to accelerate the reaction process and increase the production speed of lightweight aggregates.
[0019] Preferably, the curing environment in step S1.4 is a temperature of 20-35℃ and a relative humidity of 85%-98%, while the curing time is 19-43 hours.
[0020] By adopting the above technical solution, the curing conditions provide a suitable temperature and humidity environment for the polymerization reaction, ensuring that the slurry is fully hardened and has mechanical strength, which facilitates subsequent cutting and calcination.
[0021] Preferably, in step S1.6, the heating temperature is increased to 800-1300°C at a rate of 4-13°C / min, and held at this temperature for 1-2.5 hours.
[0022] By adopting the above technical solution, the heating rate is controlled to avoid cracking due to sudden changes in internal stress of the billet. High-temperature calcination melts the glass particles to form a liquid binder phase, while plant fibers decompose to form pores. The heat preservation stage completes the reaction, ultimately obtaining lightweight aggregate with high strength and stable structure.
[0023] Preferably, in step S3, the vibration time is 1-2.5 minutes, and the curing conditions are a temperature of 18-28℃, a relative humidity of over 90%, and a curing time of 19-43 hours.
[0024] By adopting the above technical solutions, vibration operation ensures that the concrete mixture fills the mold densely and reduces internal pores. Initial high temperature and high humidity curing promotes rapid hydration of cementitious materials, improves the early strength of concrete, and provides a foundation for long-term curing.
[0025] In summary, this application has the following beneficial effects: 1. Because this application uses a certain proportion of high-strength grade cement, self-made lightweight aggregate and mineral admixture, and because the self-made lightweight aggregate has a low apparent density and its internal uniform porous structure can form a tight interface bond with cementitious materials, it can reduce the density of concrete while maintaining ultra-high compressive strength, thereby achieving the effect of meeting the structural self-weight and strength requirements of long-span bridges and high-rise buildings.
[0026] 2. In this application, lightweight aggregate is preferably prepared using waste glass particles, fly ash, metakaolin and plant fibers. Because the waste glass particles melt to form a skeleton during high-temperature calcination, while the fly ash and metakaolin undergo a polymerization reaction under alkaline activation, and the plant fibers leave interconnected pores after combustion, lightweight, high-strength aggregate with uniform internal structure and enhanced interface is obtained. This enables the concrete to have both low density and high durability, while extending the service life of the building structure.
[0027] 3. The method of this application, through a mixing process of dry mixing followed by wet mixing, and controlling the vibration time during the molding stage, ensures that the self-made lightweight aggregate and cementitious material are evenly coated, avoiding the floating of lightweight aggregate or separation of the slurry, thus achieving a certain slump, thereby maintaining high density and uniformity of concrete during pouring, and improving construction quality and efficiency.
[0028] 4. This application utilizes waste glass and fly ash as the main raw materials to realize the resource utilization of industrial waste, reduce dependence on natural resources, and reduce environmental pollution. At the same time, compared with related lightweight aggregate preparation processes, the preparation process of this self-made lightweight aggregate has lower energy consumption, which is in line with the concept of sustainable development. Attached Figure Description
[0029] Figure 1 This is a flowchart illustrating an ultra-high strength concrete containing self-made lightweight aggregate and its preparation method, as proposed in this application. Detailed Implementation
[0030] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0031] The relevant concrete reduces its self-weight or increases its strength by adding lightweight aggregates or increasing the amount of cementitious materials. However, the interface between lightweight aggregates and cement matrix is weak and easily forms stress concentration points. At the same time, the use of a large amount of cementitious materials will lead to increased heat of hydration and increased shrinkage, resulting in a decline in the overall performance of concrete and making it difficult to meet the engineering requirements of lightweight and ultra-high strength at the same time.
[0032] This application discloses an ultra-high strength concrete containing self-made lightweight aggregate, which is made from raw materials containing the following components: high-strength grade cement, high-efficiency polycarboxylate superplasticizer, slag powder, self-made lightweight aggregate, and water; the preparation method is as follows: S1, preparation of self-made lightweight aggregate: S1.1, raw material pretreatment; S1.2, raw material mixing; S1.3, slurry preparation; S1.4, preliminary hardening; S1.5, cutting and shaping; S1.6, high-temperature calcination; S2, concrete mixing: S2.1, dry mixing; S2.2, wet mixing; S3, molding and curing.
[0033] This application uses a certain proportion of high-strength grade cement, self-made lightweight aggregate and mineral admixtures. Due to the low apparent density of the self-made lightweight aggregate and its uniform porous structure, it can form a tight interface with the cementitious material, thereby reducing the concrete density while maintaining ultra-high compressive strength. This can achieve the effect of meeting the structural self-weight and strength requirements of long-span bridges and high-rise buildings.
[0034] Example 1 This embodiment provides an ultra-high strength concrete containing self-made lightweight aggregate, which is made from raw materials containing the following components, per cubic meter of concrete: 300 kg of high-strength grade cement, 10 kg of high-efficiency polycarboxylate superplasticizer, 80 kg of slag powder, 500 kg of self-made lightweight aggregate, and 150 kg of water. The self-made lightweight aggregate is made from the following raw materials in parts by weight: 32 parts waste glass particles, 16 parts fly ash, 12 parts metakaolin, and 2 parts plant fiber.
[0035] The preparation method of the above-mentioned ultra-high strength concrete containing self-made lightweight aggregate is as follows: S1. Preparation of homemade lightweight aggregate: S1.1 Raw material pretreatment: First, collect waste glass and remove impurities before crushing it; at the same time, collect fly ash and prepare metakaolin, and cut plant fibers into small pieces for later use. Among them, the waste glass particles have a particle size of 1 mm, the fly ash has a fineness of 10% residue on a 45 μm square-hole sieve, and the metakaolin has a specific surface area of 500 m². 2 / kg, plant fiber length 5mm; S1.2 Raw material mixing: Take waste glass particles, fly ash, metakaolin and plant fiber, mix them together, pour them into a mixer and dry mix for 3 minutes to make the raw materials initially evenly mixed; S1.3, Slurry preparation: Add water and activator to the mixed dry material obtained in step S1.2, and continue stirring for 8 minutes to form a slurry; wherein, water accounts for 15% of the total mass of the mixed dry material, and activator accounts for 3% of the total mass of the mixed dry material, and the activator is a mixed solution of sodium hydroxide and sodium silicate; S1.4 Preliminary hardening: Pour the slurry obtained in step S1.3 into a mold and cure it in a curing chamber to obtain a preliminarily hardened block. The curing environment temperature was 20℃, the relative humidity was 85%, and the curing time was 19 hours. S1.5 Cutting and shaping: Take the block obtained in step S1.4 out of the mold and cut it into blanks; S1.6 High-temperature calcination: The green body obtained in step S1.5 is heated and kept at a certain temperature, and then cooled to room temperature in the furnace to obtain the self-made lightweight aggregate; The heating rate was increased to 800℃ at 4℃ / min, and the temperature was maintained at this temperature for 1 hour. S2, Concrete mixing: S2.1 Dry mixing: Take the self-made lightweight aggregate, high-strength grade cement and slag powder prepared in step S1 according to the proportion and dry mix for 3 minutes to obtain the mixed dry material; S2.2 Wet mixing: Dissolve the high-efficiency polycarboxylate superplasticizer in water, and then slowly add the solution to the mixed dry materials. Wet mix for 8 minutes to obtain the concrete mixture. S3. Molding and Curing: Pour the concrete mixture into a mold, vibrate it to form the concrete, and then cure it to obtain ultra-high strength concrete. The curing conditions were as follows: 19 hours of curing at a temperature of 18℃ and a relative humidity of over 90%, with a vibration time of 1 minute.
[0036] Example 2 This embodiment provides an ultra-high strength concrete containing self-made lightweight aggregate, which is made from raw materials containing the following components, per cubic meter of concrete: 325 kg of high-strength grade cement, 12.5 kg of high-efficiency polycarboxylate superplasticizer, 100 kg of slag powder, 650 kg of self-made lightweight aggregate, and 165 kg of water. The self-made lightweight aggregate is made from the following raw materials in parts by weight: 45 parts waste glass particles, 25 parts fly ash, 20 parts metakaolin, and 5.5 parts plant fiber.
[0037] The preparation method of the above-mentioned ultra-high strength concrete containing self-made lightweight aggregate is as follows: S1. Preparation of homemade lightweight aggregate: S1.1 Raw material pretreatment: First, collect waste glass and remove impurities before crushing it; at the same time, collect fly ash and prepare metakaolin, and cut plant fibers into small pieces for later use. The waste glass particles have a diameter of 3 mm, the fly ash has a fineness of 20% residue on a 45 μm square-hole sieve, and the metakaolin has a specific surface area of 650 m². 2 / kg, plant fiber length is 7.5mm; S1.2 Raw material mixing: Take waste glass particles, fly ash, metakaolin and plant fiber, mix them together, pour them into a mixer and dry mix for 4 minutes to make the raw materials initially evenly mixed; S1.3, Slurry preparation: Add water and activator to the mixed dry material obtained in step S1.2, and continue stirring for 10 minutes to form a slurry; Water accounts for 17.5% of the total mass of the mixed dry material, and the activator accounts for 4% of the total mass of the mixed dry material. The activator is a mixed solution of sodium hydroxide and sodium silicate. S1.4 Preliminary hardening: Pour the slurry obtained in step S1.3 into a mold and cure it in a curing chamber to obtain a preliminarily hardened block. The curing environment temperature was 27.5℃, the relative humidity was 92.5%, and the curing time was 30 hours. S1.5 Cutting and shaping: Take the block obtained in step S1.4 out of the mold and cut it into blanks; S1.6 High-temperature calcination: The green body obtained in step S1.5 is heated and kept at a certain temperature, and then cooled to room temperature in the furnace to obtain the self-made lightweight aggregate; The heating rate was increased to 1100℃ at 7.5℃ / min, and the temperature was maintained at this temperature for 1.5 hours. S2, Concrete mixing: S2.1 Dry mixing: Take the self-made lightweight aggregate, high-strength grade cement and slag powder prepared in step S1 according to the proportion and dry mix for 4 minutes to obtain the mixed dry material; S2.2 Wet mixing: Dissolve the high-efficiency polycarboxylate superplasticizer in water, and then slowly add the solution to the mixed dry materials. Wet mix for 10 minutes to obtain the concrete mixture. S3. Molding and Curing: Pour the concrete mixture into a mold, vibrate it to form the concrete, and then cure it to obtain ultra-high strength concrete. The curing conditions are as follows: curing for 30 hours at a temperature of 22.5℃ and a relative humidity of over 95%, with a vibration time of 1.5 minutes.
[0038] Example 3 This embodiment provides an ultra-high strength concrete containing self-made lightweight aggregate, which is made from raw materials containing the following components, per cubic meter of concrete: 350 kg of high-strength grade cement, 15 kg of high-efficiency polycarboxylate superplasticizer, 120 kg of slag powder, 800 kg of self-made lightweight aggregate, and 180 kg of water. The self-made lightweight aggregate is made from the following raw materials in parts by weight: 65 parts waste glass particles, 39 parts fly ash, 33 parts metakaolin, and 10 parts plant fiber.
[0039] The preparation method of the above-mentioned ultra-high strength concrete containing self-made lightweight aggregate is as follows: S1. Preparation of homemade lightweight aggregate: S1.1 Raw material pretreatment: First, collect waste glass and remove impurities before crushing it; at the same time, collect fly ash and prepare metakaolin, and cut plant fibers into small pieces for later use. The waste glass particles have a diameter of 5 mm, the fly ash has a fineness of 30% residue on a 45 μm square-hole sieve, and the metakaolin has a specific surface area of 800 m². 2 / kg, plant fiber length 10mm; S1.2 Raw material mixing: Take waste glass particles, fly ash, metakaolin and plant fiber, mix them together, pour them into a mixer and dry mix for 5 minutes to make the raw materials initially evenly mixed; S1.3, Slurry preparation: Add water and activator to the mixed dry material obtained in step S1.2, and continue stirring for 12 minutes to form a slurry; Water accounts for 20% of the total mass of the mixed dry material, and the activator accounts for 5% of the total mass of the mixed dry material. The activator is a mixed solution of sodium hydroxide and sodium silicate. S1.4 Preliminary hardening: Pour the slurry obtained in step S1.3 into a mold and cure it in a curing chamber to obtain a preliminarily hardened block. The curing environment temperature was 35℃, the relative humidity was 98%, and the curing time was 43 hours. S1.5 Cutting and shaping: Take the block obtained in step S1.4 out of the mold and cut it into blanks; S1.6 High-temperature calcination: The green body obtained in step S1.5 is heated and kept at a certain temperature, and then cooled to room temperature in the furnace to obtain the self-made lightweight aggregate; The heating rate was increased to 1300℃ at 13℃ / min, and the temperature was maintained at this temperature for 2.5 hours. S2, Concrete mixing: S2.1 Dry mixing: Take the self-made lightweight aggregate, high-strength grade cement and slag powder prepared in step S1 according to the proportion and dry mix for 5 minutes to obtain the mixed dry material; S2.2 Wet mixing: Dissolve the high-efficiency polycarboxylate superplasticizer in water, and then slowly add the solution to the mixed dry materials. Wet mix for 12 minutes to obtain the concrete mixture. S3. Molding and Curing: Pour the concrete mixture into a mold, vibrate it to form the concrete, and then cure it to obtain ultra-high strength concrete. The curing conditions were as follows: curing for 43 hours at a temperature of 28℃ and a relative humidity of over 95%, with a vibration time of 2.5 minutes.
[0040] Comparative Example 1 The comparative example refers to the content of Example 1, except that the amount of high-strength grade cement used is 210kg, and the rest is the same as Example 1; Comparative Example 2 The comparative example is the same as that in Example 1, except that the amount of high-efficiency polycarboxylate superplasticizer used is 7 kg, and the rest is the same as in Example 1. Comparative Example 3 The comparative example refers to the content of Example 1, except that the amount of self-made lightweight aggregate used is 350kg, and the rest is the same as Example 1; Comparative Example 4 The comparative example refers to the content of Example 1, except that the amount of waste glass particles in the self-made lightweight aggregate raw material is 20 parts, and the rest is the same as in Example 1. Comparative Example 5 The comparative example refers to the content of Example 1, except that in step S1.3, water accounts for 10.5% of the total mass of the mixed dry materials, and the rest is the same as in Example 1; Comparative Example 6 The comparative example refers to the content of Example 1, except that the heating temperature in step S1.6 is 700°C, and the rest is the same as Example 1.
[0041] Performance testing sample preparation: Concrete specimens were prepared for performance testing according to the formulas and preparation methods of Examples 1 to 3 and Comparative Examples 1 to 6. A set of specimens was prepared for each example and comparative example, including cubic specimens, cylindrical specimens, fresh concrete, and self-made lightweight aggregate samples. All specimens were cured under standard curing conditions to ensure the comparability of test results.
[0042] Compressive strength test: The compressive strength of the cured concrete cube specimens was tested using a hydraulic universal testing machine; the specimen size was 150mm×150mm×150mm, and the loading rate was 0.5MPa / s until the specimen failed. The maximum load was recorded and the compressive strength value was calculated; the test standard was GB / T50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete".
[0043] Dry density test: The cured concrete specimens are dried in an oven at 105℃ to constant weight, and after cooling, their mass and dimensions are measured, and the dry density is calculated; the test standard is the density test method in GB / T50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures".
[0044] Slump test: The slump test is performed on fresh concrete. A standard slump cone is used. The concrete is poured into the cone in three layers, and each layer is tamped 25 times. After smoothing, the cone is lifted vertically and the height of the concrete slump is measured. The test standard is the slump test method in GB / T50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixture".
[0045] Permeability test: The permeability of the cured cylindrical specimens was tested using a concrete permeability tester. The specimen size was Φ175mm×Φ185mm×150mm. The water pressure started at 0.1MPa and increased by 0.1MPa every 8 hours until the specimen was permeable or reached the maximum pressure. The permeability grade was recorded. The test standard was the permeability test method in GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete".
[0046] Scanning electron microscopy analysis: SEM analysis was performed on the interface between the self-made lightweight aggregate and concrete. After drying and sputtering the sample with gold, the sample was then placed under a scanning electron microscope to observe the microstructure, including pore distribution and interface bonding.
[0047] Industrial waste utilization rate calculation: By weighing and calculation, determine the percentage of waste glass and fly ash in the self-made lightweight aggregate to the total raw material mass, and compare it with the replacement rate of natural aggregate; the test standard is the waste content calculation method in GB / T25177-2010 "Recycled Coarse Aggregate for Concrete".
[0048] Performance Comparison Table: Example Conclusion: As can be seen from Examples 1-3 and Comparative Example 1, and Table 1, increasing the amount of high-strength cement can improve the overall structural density and mechanical strength of concrete. This is because cement, as the main cementitious material, increases the quantity and quality of hydration products, thereby enhancing the load-bearing capacity and integrity of the concrete matrix.
[0049] As can be seen from Examples 1-3 and Comparative Example 2, and Table 1, the high-efficiency polycarboxylate superplasticizer can improve the workability and homogeneity of concrete. The superplasticizer improves the fluidity of the slurry by dispersing cement particles and releasing the encapsulated water, thus avoiding molding defects and strength loss caused by insufficient fluidity.
[0050] Based on Examples 1-3 and Comparative Example 3, and in conjunction with Table 1, it can be seen that the amount of self-made lightweight aggregate affects the density and mechanical properties of concrete. The introduction of lightweight aggregate reduces the overall density of concrete, and the interface formed between it and the cement matrix helps stress transfer, thereby maintaining high compressive strength and durability under the premise of lightweighting.
[0051] As can be seen from Examples 1-3 and Comparative Example 4, and Table 1, the appropriate addition of waste glass particles helps to improve the skeletal function and overall stability of lightweight aggregates. During the high-temperature calcination process, the glass particles partially melt and form a supporting structure, which not only improves the strength of the aggregates but also enhances their bonding performance with cementitious materials.
[0052] Based on Examples 1-3 and Comparative Example 5, and in conjunction with Table 1, it can be seen that the appropriate amount of water used in the preparation of lightweight aggregate is crucial for slurry molding and subsequent hardening processes. Appropriate water content ensures uniform mixing and reactivity of raw materials, avoiding insufficient reaction and loose structure caused by insufficient water content.
[0053] As can be seen from Examples 1-3 and Comparative Example 6, and Table 1, the high-temperature calcination process can assist in the formation of the microstructure and properties of lightweight aggregates. By adjusting the calcination temperature, physical and chemical reactions are induced between raw materials to form a stable pore structure and a strong skeleton, thereby improving the aggregate strength and the overall performance of concrete.
[0054] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. An ultra-high strength concrete containing self-made lightweight aggregate, characterized in that, It is made from raw materials containing the following components, per cubic meter of concrete: 300-350 kg of high-strength grade cement, 10-15 kg of high-efficiency polycarboxylate superplasticizer, 80-120 kg of slag powder, 500-800 kg of self-made lightweight aggregate, and 150-180 kg of water.
2. The ultra-high strength concrete containing self-made lightweight aggregate according to claim 1, characterized in that, The self-made lightweight aggregate is made from the following raw materials in parts by weight: 32-65 parts waste glass particles, 16-39 parts fly ash, 12-33 parts metakaolin, and 2-10 parts plant fiber.
3. The ultra-high strength concrete containing self-made lightweight aggregate according to claim 2, characterized in that, The waste glass particles have a particle size of 1-5 mm; the fly ash has a fineness of no more than 30% residue on a 45 μm square hole sieve.
4. The ultra-high strength concrete containing self-made lightweight aggregate according to claim 2, characterized in that, The specific surface area of the metakaolin is 500-800 m² / kg; the length of the plant fiber is 5-10 mm.
5. A method for preparing ultra-high strength concrete containing self-made lightweight aggregate, characterized in that, The ultra-high strength concrete containing self-made lightweight aggregate as described in any one of claims 1-4 comprises the following steps: S1. Preparation of homemade lightweight aggregate: S1.1 Raw material pretreatment: First, collect waste glass and remove impurities before crushing it; at the same time, collect fly ash and prepare metakaolin, and cut plant fibers into small pieces for later use. S1.2 Raw material mixing: Take waste glass particles, fly ash, metakaolin and plant fiber and mix them in a mixer for 3-5 minutes to make the raw materials initially evenly mixed; S1.3, Slurry preparation: Add water and activator to the mixed dry material obtained in step S1.2, and continue stirring for 8-12 minutes to form a slurry; S1.4 Preliminary hardening: Pour the slurry obtained in step S1.3 into a mold and cure it in a curing chamber to obtain a preliminarily hardened block. S1.5 Cutting and shaping: Take the block obtained in step S1.4 out of the mold and cut it into blanks; S1.6 High-temperature calcination: The green body obtained in step S1.5 is heated and kept at a certain temperature, and then cooled to room temperature in the furnace to obtain the self-made lightweight aggregate; S2, Concrete mixing: S2.1 Dry mixing: Take the self-made lightweight aggregate, high-strength grade cement and slag powder prepared in step S1 according to the proportion and dry mix for 3-5 minutes to obtain the mixed dry material; S2.2 Wet mixing: Dissolve the high-efficiency polycarboxylate superplasticizer in water, and then slowly add the solution to the mixed dry materials. Wet mix for 8-12 minutes to obtain the concrete mixture. S3. Molding and Curing: The concrete mixture is poured into a mold, vibrated to form the concrete, and then cured to obtain ultra-high strength concrete.
6. The method for preparing ultra-high strength concrete containing self-made lightweight aggregate according to claim 5, characterized in that, In step S1.3, water accounts for 15%-20% of the total mass of the mixed dry materials, while the activator accounts for 3%-5% of the total mass of the mixed dry materials.
7. The method for preparing ultra-high strength concrete containing self-made lightweight aggregate according to claim 5, characterized in that, In step S1.3, the activator is a mixed solution of sodium hydroxide and sodium silicate.
8. The method for preparing ultra-high strength concrete containing self-made lightweight aggregate according to claim 5, characterized in that, The curing environment in step S1.4 is a temperature of 20-35℃ and a relative humidity of 85%-98%, while the curing time is 19-43 hours.
9. A method for preparing ultra-high strength concrete containing self-made lightweight aggregate according to claim 5, characterized in that, In step S1.6, the heating temperature is increased to 800-1300℃ at a rate of 4-13℃ / min, and held at this temperature for 1-2.5 hours.
10. A method for preparing ultra-high strength concrete containing self-made lightweight aggregate according to claim 5, characterized in that, In step S3, the vibration time is 1-2.5 minutes, and the curing conditions are a temperature of 18-28℃ and a relative humidity of over 90%, while the curing time is controlled at 19-43 hours.